Self-Compassion Among Youth with Child Maltreatment Histories and Psychological Distress: A Scoping Review - Wong, Nikki; Kim, Katherine; Ren, Peri (Pei Rui); Liu, Wai Sun; Oh, Sehyun Shannon; Strickland, Noelle; Stewart, Sherry H.; Wekerle, Christine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objective: Focusing on youth (ages 15-24), our scoping review aims to address these questions: (1) What is the relationship between self-compassion (SC) and psychological distress in youths with child maltreatment (CM) histories? and (2) How does this relationship differ across child maltreatment types?